Comparison of quality between Hahnemuehle 2992 and Schleicher & Schuell 903 filter paper, in the preservation of dried blood for the population study of IgM and IgG antibodies to syphilis - Gomez, Juan Fidel Bencomo; Castro, Antonio J. W. de; Marti, Jordi; Prates, Sydney; Appolinário, Marco Antonio O.; Oliveira, Aquila (Brazilian Journal of Sexually Transmitted Diseases, 2009)
Introduction: the filter paper (dried blood spot DBS) as an alternative of blood sample collection shows an increased interest of scientific investigators and health assistants that search to improve massive research programs of the population. Since the opening of this possibility in the last century, many authors started their projects using dried blood spots for massive neonatal studies. Since the beginning of this century, studies and possibilities are being increased using this alternative, enlarging the epidemiologic studies that support basic care on health. Objective: to assess the filter paper quality (Hahnemuehle, 2992) for collecting blood samples for sífilis screening as an alternative to the conservation of dry blood in the laboratory using this alternative strategy and in camp studies. Methods: a design for a comparative study of quality between Schleicher and Schuell 903 paper used as golden standard- and Hahnemuehle 2992 paper was realized, for the collection and storage of dried blood for the totals antibodies (IgM and IgG) against the Treponema pallidum study, using ELISA assay (sandwich type). A hundred and forty (140) signals of absorbance of the same number of pregnant samples, with previous written consent, to register their similarity, using statistic procedures of the Test of Fisher and Student (test T) with a security value of P > 0,05. It was also compared the absorbance values of the positive cases (according a settled cut off for each plate) and sensitivity, specificity and predictive value criteria were calculated on a total of 604 pregnant of the study. Results: it was detected correspondence of sensitivity, specificity and positive predictive values, in the procedures using the two types of filter papers, as well as the value of T = 0,344331 for the analysis of the average comparison between the obtained absorbance with the two types to P < 0,001. Conclusion: it was concluded that Hahnemuehle 2992 filter paper compared with Schleicher and Schuell 903 shows significantly similar and have the same quality for the detection of totals antibodies Treponema pallidum of using ELISA test.